Early Onset Preeclampsia and Cerebral Palsy: A Double Hit Model?. Issue 4 (December 2016) - Mor, O.; Stavsky, M.; Yitshak-Sade, M.; Mastrolia, S.A.; Beer-Weisel, R.; Rafaeli-Yehudai, T.; Besser, L.; Hamou, B.; Mazor, M.; Erez, O.
Abstract : ( Am J Obstet Gynecol 2016;214:105.e1–105.e9) Premature birth, especially at <28 weeks of gestation, is the leading risk factor for the development of cerebral palsy (CP) at 2 to 3 years of age. The prevalence of CP rises in a positive correlation with the severity of premature delivery and can reach up to 15% in preterm neonates who are delivered at 24 to 27 weeks of gestation. Therefore, the aims of this study were to determine (1) the association between preeclampsia and CP and (2) the risk factors for the development of CP in these patients.